SIKAP ORANG TUA TERHADAP PROGRAM POSYANDU DI KAMPUNG MAREDAN BARAT KECAMATAN TUALANG KABUPATEN SIAK - Putri Novianti; Titi Maemunaty; Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the background, the research formulating the problem is hoe good the attitude of parents towards the posyandu program in Maredan Barat Village, Tualng District, Siak Regency.The purpose of this study was to find out hoe positive the attitudes of parents towards the Posyandu Programin Maredan Barat Village, Tualang District, Siak Regency were. This type of research is descriptive with a quantitative approach. The sampling technique used is the simple random sampling techniquen. The results and findings of the research on the attitude of parents towrds the Posyandu Program in Maredan Barat Village, Tualang District, Siak regency, Congnitive, Affective and conative indicators.Key Words: Attitude, Parents, Posyandu